2010
DOI: 10.1258/jhsrp.2009.009040
|View full text |Cite
|
Sign up to set email alerts
|

Scoping Review and Approach to Appraisal of Interventions Intended to Involve Patients in Patient Safety

Abstract: An approach for appraising interventions intended to promote patient involvement in patient safety should involve: identification of the routes by which interventions assume patients' actions might contribute to their safety; identification of the conditions that would need to be met for patients to behave and contribute as the interventions (implicitly) assume; examination of the extent to which the intervention supports fulfilment of those conditions; and consideration of the potential negative effects of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
83
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(85 citation statements)
references
References 28 publications
1
83
0
1
Order By: Relevance
“…Evidence, for example, shows that a Ôknowledge and status imbalanceÕ between patients and practitioners affects the ability of a patient to adopt safety-related behaviours. 24,46,47 Research by Peat and Entwistle et al 24 found that safety interventions which were most successful required patients and their representatives to be well informed and knowledgeable. This capacity was found to vary between individuals and to be significantly affected by educational level, income, cognitive skills and cultural differences, which might affect patients health beliefs and ability to utilize health services.…”
Section: Developing a More Critical Approach To Involvement In Patienmentioning
confidence: 99%
See 3 more Smart Citations
“…Evidence, for example, shows that a Ôknowledge and status imbalanceÕ between patients and practitioners affects the ability of a patient to adopt safety-related behaviours. 24,46,47 Research by Peat and Entwistle et al 24 found that safety interventions which were most successful required patients and their representatives to be well informed and knowledgeable. This capacity was found to vary between individuals and to be significantly affected by educational level, income, cognitive skills and cultural differences, which might affect patients health beliefs and ability to utilize health services.…”
Section: Developing a More Critical Approach To Involvement In Patienmentioning
confidence: 99%
“…This capacity was found to vary between individuals and to be significantly affected by educational level, income, cognitive skills and cultural differences, which might affect patients health beliefs and ability to utilize health services. 24 In addition, Peat et al found that many patients were uncomfortable and unwilling to challenge health professionalsÕ opinions and practice. At the collective strategic level, this power imbalance was reflected in the way that patient representatives were largely expected to work within existing systems in improving quality and safety.…”
Section: Developing a More Critical Approach To Involvement In Patienmentioning
confidence: 99%
See 2 more Smart Citations
“…29 An important tool for addressing these needs is family-centered rounds (FCRs), which represent multidisciplinary rounds at the bedside involving families and patients as active shared decision makers in conjunction with the medical team. 30,31 Although FCRs have not been studied in comanagement arrangements specifically, evidence suggests that this tool improves family centeredness and patient safety in nonsurgical patients, 32 and FCRs can likely have a similar impact on postoperative care.…”
Section: Comanagement and Qualitymentioning
confidence: 99%